MANAGEMENT OF OLIGOSPERMIA AND AZOOSPERMIA THROUGH AYURVEDA - Joshi Ravi Bankatlal; Suryavanshi S Rahul (International Journal of Applied Ayurved Research, 2017)
Infertility is a problem of global proportions affecting on an average 8-12% of couples worldwide. Out of many causes of male infertility Oligospermia and Azoospermia are the leading causes. There is no satisfactory treatment in modern medicine for the conditions. Ayurveda is the better option for these conditions. In Ayurveda terms like Kshina shukra, Alpa retasa, Kshina retasa, Shukra dosha, Bijopaghata are indicating towards Oligospermia and Ashukara shandatva, Nirbeej, Abeej are indicating towards Azoospermia. In this article we are focusing on the management of Oligospermia and Azoospermia through Ayurveda.